Internationalisation of the marketing curriculum: desired in theory but what about practice? - Archer, Catherine (Australian and New Zealand Marketing Academy, 2009)
It is generally accepted within marketing and wider higher education circles that internationalisation of the undergraduate curriculum is desired if not mandatory for universities to compete in the globalised economy. This is despite the fact that there is still no clear accepted definition or widely accepted understanding of exactly what internationalisation means. This paper reflects on the effectiveness of a major international project undertaken by marketing undergraduate students within an Australian university, working in virtual global teams. The results suggest that while students often find the experience of an attempt at real internationalisation challenging, to say the least, the learning outcomes are strengthened. This paper offers new insights into the reality of internationalisation for marketing education at curriculum level.